Cristãos e comunistas na construção da utopia : a aposta de Luiz Ignácio Maranhão Filho - Góes, Maria da Conceição Pinto de. (UFRJ, 1997)
[EN] This doctoral dissertation aims at a reconstitution of Brazilian history within the last 40 years emphasizing its social, political and cultural aspects throught the biography of the communist Luiz Ignacio Maranhao Filho - Killed by the military dictatorship in 1974 - who believed in the dialogue between Christians and communists.